A method for forming a hollow spherical composite lithium adsorbent material and applications thereof

CN118904279BActive Publication Date: 2026-10-27TIANJIN UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410969547.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-19
Publication Date
2026-10-27
Estimated Expiration
2044-07-19

AI Technical Summary

Technical Problem

[0004]然而,这些复合锂吸附材料在实际应用过程中出现三个新问题:一是由于由于聚合物材料对LIS活性吸附位点的“遮蔽效应”,导致其锂吸附容量和吸附速率双下降;二是由于无机LIS与有机聚合物之间缺少相互作用,导致其界面相容性和结构稳定较差;三是当前所报道的成型步骤较为繁琐,不易实现规模放大生产

Benefits of technology

[0019]本发明的优点和积极效果是:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118904279B_ABST
    Figure CN118904279B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of composite lithium adsorption material preparation, and relates to a molding method and application of hollow spherical composite lithium adsorption material, and preparation comprises: adding powder lithium ion sieve and catecholamine compound into a low-boiling-point solvent for dispersion to obtain a suspension; adding polysulfone into the suspension for stirring under room temperature conditions to prepare casting solution; sucking the prepared casting solution into a needle tube, taking water+ethanol co-solvent as an acceptor liquid, the volume of ethanol in the acceptor liquid being 0-20%, and the height above the liquid surface of the acceptor liquid being 10-20 cm, dropwise adding the casting solution at the height, after phase inversion, washing with pure water to obtain the hollow spherical composite lithium adsorption material. The molding method is simple and easy to implement, and the prepared hollow spherical composite lithium adsorption material has high lithium adsorption capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of composite lithium adsorbent material preparation technology, and in particular relates to a molding method and application of a hollow spherical composite lithium adsorbent material. Background Technology

[0002] Lithium, as a crucial element supporting the national new energy strategy, is widely recognized as a "green energy metal" and "white oil" that drives global progress, and is extensively used in new energy vehicles, aerospace, and other fields. Seawater, geothermal water, and salt lake brines contain over 60% of the Earth's total lithium resources, making the efficient development of these resources of significant economic value and strategic importance.

[0003] Adsorption is currently recognized as the most promising method for lithium extraction from marine brine. Its core technology utilizes the structure of inorganic lithium ion sieves (LIS) adsorbents to extract lithium. + The "memory function" of Li + Separation and enrichment. However, LIS usually exists in powder form, and its industrial applications are limited by problems such as easy agglomeration, easy loss, and difficulty in recycling. To solve these industrial problems, composite lithium adsorbent materials in granular, foam, sponge, flat film, and fibrous forms have been prepared by molding techniques such as immersion phase inversion, freeze drying, and electrospinning.

[0004] However, these composite lithium adsorbent materials encounter three new problems in practical applications: First, the "masking effect" of polymer materials on the active adsorption sites of LIS leads to a decrease in both lithium adsorption capacity and adsorption rate; second, the lack of interaction between inorganic LIS and organic polymers results in poor interfacial compatibility and structural stability; and third, the currently reported molding steps are relatively cumbersome, making it difficult to scale up production. These problems further limit the practical application of current composite lithium adsorbent materials. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a method for forming and applying a hollow spherical composite lithium adsorbent material. By in-situ functional modification of powdered lithium ion sieves and by solvent evaporation-induced phase transformation, a hollow spherical composite lithium adsorbent material with high lithium adsorption capacity is obtained.

[0006] The technical solution adopted by this invention to solve the technical problem is:

[0007] This invention provides a method for molding hollow spherical composite lithium adsorbent materials. This method utilizes solvent evaporation to induce phase transformation, and the specific operation is as follows:

[0008] (1) Add 1.0-6.0 wt% of powdered lithium ion sieve and 0.05-0.2 wt% of catecholamine compounds to a low-boiling-point solvent, and disperse the powdered lithium ion sieve under ultrasonic treatment at 400-600W for 20-40 min to obtain a suspension;

[0009] (2) Add 2.0 to 6.0 wt% of polysulfone to the suspension and stir at room temperature (20 to 25°C) for 2 to 5 hours to prepare a casting solution;

[0010] (3) The casting solution obtained in step (2) is drawn into a syringe. Water and ethanol are used as the receiving solution, with the volume of ethanol in the receiving solution being 0-20%. The casting solution is added dropwise at a height of 10-20 cm above the surface of the receiving solution. After phase inversion for 1-2 hours, the solution is thoroughly washed with pure water to obtain hollow spherical composite lithium adsorbent material. Adding an appropriate proportion of ethanol to the water helps to reduce the surface tension of the receiving solution, thereby controlling the wall thickness and microporous structure of the hollow spherical composite lithium adsorbent material. However, when the ethanol content exceeds 20%, the wall thickness is too small, resulting in a flattened sheet shape.

[0011] Furthermore, the powder lithium ion sieve is a titanium-based lithium ion sieve, a manganese-based lithium ion sieve, an aluminum-based lithium ion sieve, etc.

[0012] Furthermore, the casting solution contains 3.0–5.0 wt% polysulfone.

[0013] Furthermore, the volume of ethanol in the receiving liquid is 0-10.0%.

[0014] Furthermore, the catecholamine compounds are used to modify the hydrophilic function of the powder ion sieve through oxidation-self polymerization. The catecholamine compounds are one or more of dopamine hydrochloride, catechol, tannic acid, gallic acid, and m-phenylenediamine.

[0015] Furthermore, the low-boiling-point solvent is one or more of dichloromethane, carbon disulfide, chloroform, and tetrahydrofuran.

[0016] Furthermore, polysulfone serves as a carrier for coating lithium-ion sieves in powder form. Polysulfone can also be polyvinyl chloride or polyvinylidene fluoride.

[0017] Another aspect of the present invention provides the application of the hollow spherical composite lithium adsorbent material prepared by the molding method described above in lithium adsorption.

[0018] Furthermore, the hollow spherical composite lithium adsorbent material was dispersed in a lithium-containing solution with a solid-liquid ratio of 1:100 to 1:200, and the adsorption capacity was tested using an inductively coupled plasma atomic emission spectrometer.

[0019] The advantages and positive effects of this invention are:

[0020] (1) This invention utilizes green biomimetic materials to achieve in-situ functional modification of powder ion sieves during the molding process, and obtains a hollow spherical composite lithium adsorbent material by solvent evaporation-induced phase transformation. The molding method is simple and easy to implement. The lithium ion sieves in the hollow spherical composite lithium adsorbent material tend to be enriched on the inner and outer surfaces of the hollow spheres, exhibiting a lithium adsorption capacity comparable to that of powder lithium ion sieves. Moreover, after being circulated in actual underground brine for 5 cycles, it can still maintain more than 90% of the adsorption capacity, showing good cycle stability.

[0021] (2) This molding technology is universal and can be applied to titanium-based, manganese-based, and aluminum-based powder lithium ion sieves. It can even be further extended to the molding and preparation of composite adsorption materials for adsorbing bromine, rubidium, cesium, and strontium ions. It can provide technical support for the industrialization of lithium extraction from sea brine and has great prospects for industrial application. Attached Figure Description

[0022] Figure 1 This is a photograph of the hollow spherical composite lithium adsorbent material prepared in Example 1 of the present invention.

[0023] Figure 2 This is a particle size distribution diagram of the hollow spherical composite lithium adsorbent material prepared in Example 1 of the present invention;

[0024] Figure 3 The graph shows the lithium adsorption performance of the hollow spherical composite lithium adsorbent material prepared in Example 1 of this invention.

[0025] Figure 4 This is a photograph of the hollow spherical composite lithium adsorbent material prepared in Example 2 of the present invention.

[0026] Figure 5 The graph shows the lithium adsorption performance of the hollow spherical composite lithium adsorbent material prepared in Example 2 of this invention.

[0027] Figure 6 The graph shows the lithium adsorption performance of the hollow spherical composite lithium adsorbent material prepared in Example 3 of this invention.

[0028] Figure 7 The lithium adsorption performance of the hollow spherical composite lithium adsorbent material prepared in Comparative Example 1 is shown in the figure.

[0029] Figure 8 A physical image of the hollow spherical composite lithium adsorbent material prepared in Comparative Example 2;

[0030] Figure 9 The lithium adsorption performance of the hollow spherical composite lithium adsorbent material prepared in Comparative Example 2 is shown in the figure.

[0031] Figure 10This is a comparison diagram of the structural stability of hollow spherical composite lithium adsorbent materials prepared by method (A) in Example 1 and method (B) in Comparative Example 2 of the present invention.

[0032] Figure 11 A photograph of the hollow spherical composite lithium adsorbent material prepared in Comparative Example 3;

[0033] Figure 12 The lithium adsorption performance of the hollow spherical composite lithium adsorbent material prepared for Comparative Example 3 is shown in the figure. Detailed Implementation

[0034] The present invention will be further described in detail below through specific embodiments. The following embodiments are merely descriptive and not limiting, and should not be used to limit the scope of protection of the present invention.

[0035] Example 1

[0036] A method for molding a hollow spherical composite lithium adsorbent material, the specific operation of which is as follows:

[0037] (1) Add 4.0 wt% of titanium-based lithium ion sieve and 0.1 wt% of hydrochloric acid-dopamine to dichloromethane, a low-boiling-point solvent, and disperse the powdered lithium ion sieve under 500W ultrasonication for 30 min to obtain a suspension;

[0038] (2) Add 4.0 wt% of polysulfone to the suspension obtained in step (1) and stir at room temperature (20°C) for 5 h to prepare casting solution;

[0039] (3) The casting solution obtained in step (2) is drawn into a syringe. Using pure water as the receiving liquid, the casting solution is dripped dropwise at a height of 20 cm above the surface of the receiving liquid. After 1 hour of phase inversion, it is thoroughly washed with pure water to obtain hollow spherical composite lithium adsorbent material (HTO / DA / PSf) (see Appendix). Figure 1 Its average particle size is 1.5–2.5 mm (see appendix). Figure 2 ).

[0040] Figure 3 HTO / DA / PSf in the text refers to hollow spherical composite lithium adsorbent material containing a hydrophilically modified titanium-based lithium ion sieve. HTO refers to the titanium-based lithium ion sieve; DA refers to the hydrophilic modifier dopamine; and PSf refers to the polysulfone coating material.

[0041] Application Example 1

[0042] The hollow spherical composite lithium adsorbent material obtained in Example 1 was dispersed in 25.0 mg / L solution at a solid-liquid ratio of 1:100 at pH 12. -1 The lithium-containing solution was tested using inductively coupled plasma atomic emission spectrometry (ICP-AES), and its equilibrium adsorption capacity at 298.15 K was calculated to be 25.68 mg·g⁻¹. -1 (See appendix) Figure 3 It is comparable to powder lithium ion sieves.

[0043] Example 2

[0044] A method for molding a hollow spherical composite lithium adsorbent material, the specific operation of which is as follows:

[0045] (1) Add 4.0 wt% of titanium-based lithium ion sieve and 0.1 wt% of hydrochloric acid-dopamine to dichloromethane, a low-boiling-point solvent, and disperse the powdered lithium ion sieve under 500W ultrasonication for 30 min to obtain a suspension;

[0046] (2) Add 4.0 wt% polysulfone to the suspension obtained in step (1) and stir at room temperature (20°C) for 3 h to prepare casting solution;

[0047] (3) The casting solution obtained in step (2) is drawn into a syringe. Using a co-solvent with a volume ratio of ethanol to water of 2:98 as the receiving liquid, the casting solution from step (2) is dripped dropwise at a height of 15 cm above the surface of the receiving liquid. After a phase inversion of 2 hours, the mixture is thoroughly washed with pure water to obtain a hollow spherical composite lithium adsorbent material (see Appendix). Figure 4 ).

[0048] Application Example 2

[0049] The hollow spherical composite lithium adsorbent material obtained in Example 2 was dispersed at a solid-liquid ratio of 1:100 in 25.0 mg·L⁻¹ solution at pH = 12. -1 The lithium-containing solution was tested using inductively coupled plasma atomic emission spectrometry (ICP-AES), and its equilibrium adsorption capacity at 298.15 K was calculated to be 25.71 mg·g⁻¹. -1 (See appendix) Figure 5 ).

[0050] Example 3

[0051] A method for molding a hollow spherical composite lithium adsorbent material, the specific operation of which is as follows:

[0052] (1) Add 5.0 wt% of titanium-based lithium ion sieve and 0.1 wt% of m-phenylenediamine to dichloromethane, a low-boiling-point solvent, and disperse the powdered lithium ion sieve under ultrasonic treatment at 500 W for 30 min to obtain a suspension.

[0053] (2) Add 4.0 wt% polysulfone to the suspension obtained in step (1) and stir at room temperature (20°C) for 5 h to prepare casting solution;

[0054] (3) The casting solution obtained in step (2) is drawn into a syringe. Using pure water as the receiving liquid, the casting solution from step (2) is dripped dropwise at a height of 20 cm above the surface of the receiving liquid. After 2 hours of phase inversion, the mixture is thoroughly washed with pure water to obtain hollow spherical composite lithium adsorbent material (HTO / MPD / PSf) (see...). Figure 6 ).

[0055] Figure 6 HTO / MPD / PSf refers to hollow spherical composite lithium adsorbent materials containing hydrophilically modified titanium-based lithium ion sieves. HTO refers to titanium-based lithium ion sieves; MPD refers to the hydrophilic modifier m-phenylenediamine; and PSf refers to polysulfone coating material.

[0056] Application Example 3

[0057] The hollow spherical composite lithium adsorbent material obtained in Example 2 was dispersed at a solid-liquid ratio of 1:100 in 25.0 mg·L⁻¹ solution at pH = 12. -1 The lithium-containing solution was tested using inductively coupled plasma atomic emission spectrometry (ICP-AES), and its equilibrium adsorption capacity at 298.15 K was calculated to be 24.55 mg·g⁻¹. -1 (See appendix) Figure 6 ).

[0058] Comparative Example 1

[0059] To highlight the superior performance of the hollow spherical lithium composite adsorbent material prepared by this method, a planar mixed matrix lithium adsorbent material was prepared using the existing breathing pattern method. The specific steps and results are as follows:

[0060] (1) At 298.15 K, 1.0 g of titanium-based lithium ion sieve was placed in a 0.1 wt% dopamine-Tris solution with pH = 8.50 for 5 h for modification. It was then washed thoroughly with deionized water until the supernatant was clear and transparent and the total organic carbon content was 0. It was then dried at 333.15 K.

[0061] (2) Add 4.0 wt% of the dopamine-modified lithium ion sieve powder from (1) to the low-boiling-point solvent dichloromethane, and disperse the lithium ion sieve powder under 500W ultrasonication for 30 min.

[0062] (3) Add 4.0 wt% of polysulfone to the suspension prepared in step (2) and stir at room temperature (20°C) for 5 h;

[0063] (4) Immerse a 300-mesh nylon screen in the casting solution and prepare a flat mixed matrix lithium adsorbent material by means of the breathing pattern method under the conditions of 90% humidity and 293.15K temperature.

[0064] Application Comparative Example 1

[0065] At 298.15 K, the plate-shaped mixed matrix lithium adsorbent material obtained in Comparative Example 1 was placed at a solid-liquid ratio of 1:100 in a solution of pH 12.0 and Li. + The initial concentration was 25.0 mg·L⁻¹. -1In a LiCl solution, adsorption was carried out until equilibrium was reached; the equilibrium adsorption capacity at 298.15 K was measured and calculated using inductively coupled plasma atomic emission spectrometry (ICP-AES) to be 22.18 mg·g⁻¹. -1 (See appendix) Figure 7 The performance of the hollow spherical lithium composite adsorbent prepared by this method is lower than that of the material itself (equilibrium adsorption capacity of 25.68 mg·g⁻¹). -1 ).

[0066] Comparative Example 2

[0067] A method for molding a hollow spherical composite lithium adsorbent material, the specific steps of which are as follows:

[0068] (1) 4.0 wt% of titanium-based lithium ion sieve was added directly to dichloromethane, a low-boiling-point solvent, without hydrophilic functional modification, and the powder lithium ion sieve was dispersed under 500W ultrasonication for 30 min.

[0069] (2) Add 4.0 wt% of polysulfone to the suspension prepared in step (1) and stir at room temperature (20°C) for 5 h;

[0070] (3) The casting solution obtained in step (2) is drawn into a syringe. Using pure water as the receiving liquid, the casting solution from step (2) is dripped dropwise at a height of 20 cm above the surface of the receiving liquid. After a phase inversion of 1 hour, the mixture is thoroughly washed with pure water to obtain hollow spherical composite lithium adsorbent material (HTO / PSf) (see Appendix). Figure 8 ).

[0071] Figure 9 HTO / PSf refers to hollow spherical composite lithium adsorbent material containing unmodified titanium-based lithium ion sieves, where HTO refers to titanium-based lithium ion sieves and PSf refers to polysulfone coating material.

[0072] Application Comparative Example 2

[0073] The hollow spherical composite lithium adsorbent obtained in Comparative Example 2 was dispersed at a solid-liquid ratio of 1:100 in 25.0 mg·L⁻¹ solution at pH = 12. -1 In the lithium-containing solution, adsorption was complete. The equilibrium adsorption capacity at 298.15 K was measured and calculated using inductively coupled plasma atomic emission spectrometry (ICP-AES) to be only 17.76 mg·g⁻¹. -1 (See appendix) Figure 9 However, due to the lack of interfacial interaction between the powder ion sieve and polysulfone, the powder ion sieve in the hollow spherical composite lithium adsorbent material leaks severely at adsorption equilibrium (see Appendix). Figure 10 The result indicates that the structural stability is poor, and it is not as good as the hollow spherical composite lithium adsorbent material prepared by this method.

[0074] Comparative Example 3

[0075] The only difference from Example 1 is that the co-solvent with a volume ratio of ethanol to water of 22:78 in step (3) is the receiving liquid.

[0076] Figure 11 The image shows the hollow spherical composite lithium adsorbent material prepared in Comparative Example 3. When the ethanol content exceeds 20%, the spherical wall thickness is too small, resulting in a flattened sheet shape.

[0077] Application Comparative Example 3

[0078] The hollow spherical composite lithium adsorbent material prepared in Comparative Example 3 was dispersed at a solid-liquid ratio of 1:100 in 25.0 mg·L⁻¹ solution at pH = 12. -1 The lithium-containing solution was tested using inductively coupled plasma atomic emission spectrometry (ICP-AES) and the equilibrium adsorption capacity at 298.15 K was calculated to be 19.90 mg·g⁻¹. -1 (See appendix) Figure 12 The adsorption effect was far inferior to that of Example 1.

[0079] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several modifications and improvements can be made without departing from the inventive concept, and these all fall within the protection scope of the present invention.

Claims

1. A method for forming a hollow spherical composite lithium adsorbent material, characterized in that, This molding method utilizes solvent evaporation to induce phase transformation, and the specific operation is as follows: (1) 1.0~6.0 wt% of powdered lithium ion sieve and 0.05~0.2 wt% of catecholamine compound or m-phenylenediamine are added to a low-boiling-point solvent and dispersed under ultrasonication at 400~600W for 20-40 min to obtain a suspension; the low-boiling-point solvent is one or more of dichloromethane, carbon disulfide and trichloromethane; (2) Add 2.0~6.0 wt% of polysulfone to the suspension and stir at room temperature (20~25℃) for 2~5 h to prepare casting solution; (3) The casting solution obtained in step (2) is drawn into a syringe. Water and ethanol are used as the receiving liquid. The volume of ethanol in the receiving liquid is 0-20%. The casting solution is dripped into the syringe at a height of 10-20 cm above the surface of the receiving liquid. After phase inversion for 1-2 hours, the solution is thoroughly washed with pure water to obtain hollow spherical composite lithium adsorbent material.

2. The molding method according to claim 1, characterized in that, The casting solution contains 3.0~5.0 wt% polysulfone.

3. The molding method according to claim 1, characterized in that, The volume of ethanol in the receiving solution is 0~10.0%.

4. The molding method according to claim 1, characterized in that, The catecholamine compound is dopamine hydrochloride.

5. The molding method according to claim 1, characterized in that, Polysulfone can be replaced with polyvinyl chloride or polyvinylidene fluoride.

6. The application of the hollow spherical composite lithium adsorbent material prepared by the molding method according to any one of claims 1 to 5 in lithium adsorption.

Citation Information

Patent Citations

  • Polyvinylidene fluoride / polydopamine modified nanometer kaolin hollow fiber composite film preparation method

    CN105233705A

  • Prussian blue composite adsorbent for selectively extracting cesium as well as preparation method and application of Prussian blue composite adsorbent

    CN117299097A